2018
DOI: 10.1186/s13065-018-0484-4
|View full text |Cite
|
Sign up to set email alerts
|

Planting and seasonal and circadian evaluation of a thymol-type oil from Lippia thymoides Mart. & Schauer

Abstract: BackgroundThe oil and extracts of Lippia thymoides have been used for various medicinal and food applications. Entrepreneurs in the Amazon have been considering the economic exploitation of this plant. The present study evaluated the influence of the seasonal and circadian rhythm on the yield and composition of the essential oil of leaves and thin branches of a Lippia thymoides specimen cultivated in Abaetetuba, State of Pará, Brazil. The constituents of the oils were identified by GC and GC–MS and with the ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
11
0
2

Year Published

2019
2019
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 21 publications
(27 reference statements)
2
11
0
2
Order By: Relevance
“…thymoides described in this work can be a natural source with potential for the development of new phytotherapics for the treatment of Alzheimer's disease or even be included in the diet of people with Alzheimer's. It is important to emphasize that in our previous work [47] it was shown that this specimen presents thymol as the majority constituent of essential oil throughout its seasonal cycle, which reinforces its viability as a source of obtaining this component.…”
Section: Resultssupporting
confidence: 67%
“…thymoides described in this work can be a natural source with potential for the development of new phytotherapics for the treatment of Alzheimer's disease or even be included in the diet of people with Alzheimer's. It is important to emphasize that in our previous work [47] it was shown that this specimen presents thymol as the majority constituent of essential oil throughout its seasonal cycle, which reinforces its viability as a source of obtaining this component.…”
Section: Resultssupporting
confidence: 67%
“…Multivariate analysis was performed according to a reported procedure, [63–65] using the Minitab® software. The variables used were the chemical compounds of the essential oil and aroma of Bignonia nocturna leaves and stems (≥0.1 %) obtained by HD, SD and SDE, thus forming a matrix of 12 (samples)×10 (variables).…”
Section: Methodsmentioning
confidence: 99%
“…In addition, Pinto et al (2013) [27] evaluated the methanolic extracts of leaves, branches, and flowers of L. thymoides, which exhibited antimicrobial activity against Staphylococcus aureus; these results corroborated its traditional use in the treatment of infectious diseases [27]. Despite the importance of this species in traditional medicine, few studies have reported the chemical composition of L. thymoides essential oil [28][29][30][31].…”
Section: Introductionmentioning
confidence: 91%